The Secondary Lifting Performance of Crawler Crane Under Delay Coefficient Control Strategy - Jin Zhang; Ranheng Du; Kuo Zhang; Yin Zhang; Ying Li; Xing Chen (Machines)
Crawler cranes are mobile lifting equipment used in the process of hoisting goods. After the initial lifting, the crane may need a secondary lift due to adjustments in the position or height of the load. Addressing the common issue of load slipping during the secondary lift caused by hydraulic motor reversal, this study proposes a control strategy applicable to crawler crane secondary lifting. Initially establishing the dynamic characteristics of the secondary lift system, incorporating a delay coefficient, and matching motor pressure build-up with memory pressure, the strategy considers a variable pump input current control to identify the relationship between motor pressure build-up and brake release. Analyzing the dynamic characteristics of secondary lifting under different conditions, this study resolves the issue of hydraulic motor reversal during the second lift caused by heavy loads. The results of this study on crawler crane secondary lifting indicate that, when using a delay coefficient of 0.70 and releasing the brake, no slip phenomenon occurred during the secondary lift process under different load conditions, categorized as 200 tons, 600 tons, and 1000 tons. This ensures the stability and transition quality of the secondary lift, providing theoretical guidance for the control of the crawler crane secondary lifting.